1998
DOI: 10.1093/nar/26.10.2359
|View full text |Cite
|
Sign up to set email alerts
|

Cytarabine-induced destabilization of a model Okazaki fragment

Abstract: Cytarabine is a potent anticancer drug that interferes with elongation of the lagging strand at the replication fork during DNA synthesis. The effects of cytarabine substitution on the structural and thermodynamic properties of a model Okazaki fragment were investigated using UV hyperchromicity and 1H NMR spectroscopy to determine how cytarabine alters the physicochemical properties of Okazaki fragments that are intermediates during DNA replication. Two model Okazaki fragments were prepared corresponding to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 20 publications
2
30
0
Order By: Relevance
“…It has been reported that internalized AraC or dFdC in DNA changes the structure and stability of DNA (23,24) and inhibits DNA replication (25). It was also shown that AraC within DNA templates can block the Klenow fragment of DNA pol I and T4 DNA polymerase (26).…”
Section: In Vitro Biochemical Studies Of Pol G With Nucleoside Analogmentioning
confidence: 99%
“…It has been reported that internalized AraC or dFdC in DNA changes the structure and stability of DNA (23,24) and inhibits DNA replication (25). It was also shown that AraC within DNA templates can block the Klenow fragment of DNA pol I and T4 DNA polymerase (26).…”
Section: In Vitro Biochemical Studies Of Pol G With Nucleoside Analogmentioning
confidence: 99%
“…The major action of Ara-C is inhibition of DNA synthesis, so it is highly toxic for dividing cells (Sarraf et al 1993;Gmeiner et al 1998;Courtney and Coffey 1999). Although there is an extensive literature on the use of anti-mitotic drugs to study neurodevelopment and neurotoxicology, there are only a limited number of studies that have used anti-mitotics to develop animal models for schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Thermodynamic studies indicate nucleoside analogs having anticancer activity as a consequence of misincorporation into DNA may destabilize the duplex 2,21,46 while NMR structural studies indicate analog substitution causes local structural perturbations. 2,22,47 These data are useful in rationalizing how nucleoside analogs, such as dFdC, AraC, and FdU, perturb DNA-protein interactions in a way that leads to cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last several years, there has been increasing knowledge concerning how dFdCTP and AraCTP incorporation into DNA affects DNA structure and stability. 2,21,22 At the same time, the roles of specific proteins that interact with analog-substituted DNA in a different manner than native DNA have been described. 3,23 Collectively, these studies are providing insight into the structure-function relationships that are responsible for the anticancer activities resulting from incorporation of dFdC, AraC, and other antipyrimidines into DNA.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation